Liberating narratives: museums and Web 2.0 - Babić, Darko muzeolog; Miklošević, Željka (2009)
The paper attempts to put into relation the social web environment and museums. In a retrospective view on the formation and dissemination of knowledge in museums, discernible are several stages also connected to the public access and the social role of these cultural institutions. Virtual environment is seen yet as another stage which with the Web 2.0 technologies creates possibilities for a redefined role of the museum at a more socially profound level that might be characterized as multivocal and collaborative.
ENG